SEXUAL DYSFUNCTION AMONG WOMEN AT FOUR TO SIX MONTHS POSTPARTUM: A STUDY IN A PRIMARY CARE SETTING - Norafini Salamon; Syahnaz Mohd Hashim; Norfazilah Ahmad; Suzaily Wahab (Malaysian Journal of Public Health Medicine, 2020)
Sexual dysfunction in women is a significant health problem that harms marriage stability. Women in the Western countries were reportedly being affected by this condition after childbirth but the magnitude of the problem in our local setting is still unknown. The aim of this cross-sectional study was to determine the prevalence of women with sexual dysfunction at four to six months postpartum and its possible risk factors in an urban primary care setting. The participants were given a set of questionnaire, consisting of three parts; i) sociodemographic and maternal characteristics ii) Malay version of Female Sexual Function Index and iii) Malay DASS-21 questionnaire. Responses from 249 women were analyzed. More than half (57.0%,n=142) were found to have sexual dysfunction. The most prevalent types of sexual dysfunction reported by the affected women were sexual satisfaction disorder (98.6%), followed by arousal disorder (58.5%) and lubrication disorder (28.9%). Three factors were found to be significantly associated with sexual dysfunction; household income of less than RM2000 (adj OR = 0.31, 95% CI 0.14, 0.70), Malay ethnic group (adj OR = 1.93,95% CI 1.02, 3.66) and breastfeeding (adj OR = 2.24,95% CI 1.03, 4.85). In conclusion, the prevalence of sexual dysfunction in the postpartum period was considerably high. Efforts should be made to incorporate sexual health as part of the routine postnatal assessment in primary care practice.